Challenges and Opportunities to the Foreign Policy of Pakistan in the Contemporary Era - Hussain, Mumtaz; Yousafzai, Atif Ur Rahman; Naseem, Farwa (Annals of Human and Social Sciences, 2023)
Pakistan came into existence in 1947 and faced plenty of challenges and troubles. Therefore, the country has been striving hard to get on the right track with domestic and foreign policies due to insufficient and ineffective policies leading to further grave issues. The chequered civil-military relations always led to a divergent stance over the country's strategic interests. In Pakistan, normative ideals, corporate elites, and public opinion played a role in their interest in the country's foreign policy. Moreover, the information revolution also profoundly affects policy, which sometimes poses a threat rather than an opportunity, such as in hybrid warfare, anti-narrative building, and radicalizing the youth. Besides, nontraditional security threats such as climate change, its shocking effect, terrorism, national disasters, political uncertainty, and financial predicament are significant challenges to Pakistan's foreign policy in the current scenario. On the other hand, the world order is turning into multipolar, and regional economies are emerging, creating valuable opportunities if Pakistan can secure its national interest through an effective foreign policy.